SIMULTANEOUS SEPARATION OF THIRD AND FOURTH GENERATION SIX FLUOROQUINOLONES BY ISOCRATIC HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY: APPLICATION TO MOXIFLOXACIN DETERMINATION IN PHARMACEUTICAL DOSAGE FORMS - P.RAVISANKAR; G.DEVALARAO (International Journal of Pharma and Bio Sciences, 2013)
This study was designed to develop and validate a simple, sensitive, precise, economical, reproducible and accurate isocratic reversed phase high performance liquid chromatographic method for separation and analysis of 6 fluoroquinolones in bulk and their pharmaceutical dosage forms. The effects of mobile phase composition, buffers, pH, and acetonitrile concentrations were investigated on the separation of third generation fluoroquinolones (levofloxacin, sparfloxacin, balofloxacin) and fourth generation fluoroquinolones ( gatifloxacin, moxifloxacin, prulifloxacin) were assayed without any interference. RP-HPLC method was developed by using Welchrom C18 Column (4.6 X 250mm, 5µm), Shimadzu LC-20AT prominence liquid chromatograph. The mobile phase consisting of phosphate buffer pH-3.1 and acetonitrile in the portion of 70:30 v/v. Isocratic elution at a flow rate of 1ml/min was employed. The responses were measured at 293 nm using Shimadzu SPD-20A prominence UV-Vis detector. The method was successfully applied to Moxifloxacin pharmaceutical dosage form. During method validation parameters such as linearity, precision, specificity, robustness, ruggedness were evaluated from spiked tablet samples according to ICH guidelines, which remained within acceptable limits. The proposed method can also be extended for the determination of other five fluoroquinolones or their combinations. This method provides a fast simple method with good retention, excellent peak shape and high resolution.